SCIENTIFICALLY BASED METHODS OF THE TRAINING PROCESS IN THE TRAINING OF HIGHLY QUALIFIED ATHLETES - Aisultan Zheldibay (Modern American Journals, 2025)
The article summarizes scientifically based approaches to building the training process in Kazakh kuresi for highly qualified athletes. Based on UWW regulatory requirements and modern sports science data, the key components of training are systematized: periodization, development of specific performance (anaerobic power, strength endurance, explosive power), technical and tactical training, load and recovery monitoring (sRPE, heart rate/HRV), and individualization elements. A practice-oriented model of micro-meso-macrocycles for the stages of the preparatory and pre-competition periods is proposed, specifying control criteria and controlled load variables.
Keywords: Qazaq kuresi, periodization, load monitoring, sRPE, HRV, strength, anaerobic training, elite athletes, UWW.